Challenges of Seaweed Cultivation in Nusa Penida for Economic, Tourism, and Environmental Sustainability - Putra, Ida Bagus Gede Karyambara (Bali Tourism Board, 2023)
Seaweed production in Indonesia is distributed across 23 provinces. The top five provinces in seaweed production, according to rankings, are South Sulawesi, East Nusa Tenggara, North Kalimantan, Central Sulawesi, and West Nusa Tenggara. Among the dozens of seaweed-producing provinces, Bali has the potential for seaweed cultivation, supported by a vast marine area of 95,000 km2. The Nusa Penida sub-district of Klungkung Regency, the community shows interest in becoming seaweed farmers. The accessibility for seaweed farming in Nusa Penida is due to its location approximately ten nautical miles southeast of Bali, and its coastal area is recognized as a